New efficient synthesis of polysubstituted 3,4-dihydroquinazolines and 4H-3,1-benzothiazines through a Passerini/Staudinger/aza-Wittig/addition/nucleophilic substitution sequence - Zhao, Long; Yang, Mao-Lin; Liu, Min; Ding, Ming-Wu (Beilstein Journal of Organic Chemistry, 2022)
A new efficient synthesis of polysubstituted 3,4-dihydroquinazolines and 4H-3,1-benzothiazines via sequential Passerini/Staudinger/aza-Wittig/addition/nucleophilic substitution reaction has been developed. The three-component Passerini reactions of 2-azidobenzaldehydes 1, benzoic acid (2), and isocyanides 3 produced the azide intermediates 4, which were treated sequentially with triphenylphosphine, isocyanates (or CS2), and secondary amines to give polysubstituted 3,4-dihydroquinazolines 8 and 4H-3,1-benzothiazines 11 in good overall yields through consecutive Passerini/Staudinger/aza-Wittig/addition/nucleophilic substitution reactions.
Keywords: aza-Wittig reaction; 3,4-dihydroquinazoline; 4H-3,1-benzothiazine; nucleophilic substitution; Passerini reaction; Staudinger reaction